PERFORMANCE OF BEAM CONTAINING BAMBOO ASH IN CONCRETE MIXTURE - Adnan, Suraya Hani; Mohd Satti, Nadia Syuhada; Jameli, Mohammad Ikhmal; Osman, Mohamad Hairi; Jamellodin, Zalipah; Alisibramulisi, Anizahyati (2023)
The cement and construction industry's smokestacks are among the most significant contributors to poor air quality, especially in urban areas. The Portland cement production sector was currently under scrutiny due to the enormous amounts of carbon dioxide emitted. The objective of this study is to determine the performance of concrete by flexural of the beam and compressive strength with a percentage of bamboo ash replacement from cement are 0%,5%,10%,15%, and 20%. The concrete mixture was designed by the department of environment (DOE) mix method with the flexural testing method according to ASTM C293 and compressive strength according to BS 1881-116:1983. The study's findings indicated that bamboo ash was capable of improving compressive strength performance at a replacement percentage of 5% for the BACR5 sample, and nearly the same trend happened for flexural testing at the same percentage. Thus, this study can be expanded to include a higher proportion of cement replacement, as the trend indicates an improvement for a 20% replacement rate, termed BACR20.